Modeling of chronic generalized periodontitis in laboratory animals (literature review) - O. V. Kopchak; N. S. Marchenko; Ya. V. Yanishevska (Medičnì Perspektivi)
Modern experiments in the study of periodontal deseas are aimed at improving the effectiveness of innovative methods of early diagnosis, treatment and prevention of this disease in patients. The conducted analysis of the literature showed that the disorder of microcirculation occupies one of the leading places in the pathogenesis of periodontitis. Disruption of the microcirculatory bed, based on the dyscirculatory changes of the capillary blood flow is accompanied by a decrease in the intensity of blood filling of vessels, their spasm. These changes, in case of chronization, include tissue disorders of the ischemic nature, up to the development of a capillary stasis. This can lead to disorder in gas exchange, trophism and pathomorphological damage to periodontal tissues. This type of change is most typical for age-related, traumatic, vascular, and stress-induced models. Morphological lesions in the vessels, namely ischemic phenomena were most pronounced in them. Microscopically, this was manifested in the heterogeneity of the epithelial layer, the thickening of individual layers, the detachment of the epithelial lining of the mucosa. As for the basal layer, the most common was the vacuolization of cells, the appearance of a significant number of cells that lacked nuclei (pathology, indicating a decrease in functional activity, impaired regenerative properties of the cell), expansion of intercellular contacts, a sign of tissue edema. In the basal membrane (function - dissociation of the epithelium from the actual lining of the mucous membrane), collagen fibers were loose, hypertrophic, their hyperplasia was observed, neutrophil leukocytes, lymphocytes, histocytes were found between the fibers, this testified to changes in cells. Some models lack a clinical picture of chronic hyperplastic periodontitis. The disorders consisted of changes in normal metabolism in periodontal tissues, decreased immune function, changes in morphological structure without induction of the inflammatory process.